Multiple Microcontroller Programming Using the SWD Interface - Bogdanov, Lubomir (2020 XXIX International Scientific Conference Electronics (ET), 2020)
Many microcontrollers nowadays are based on ARM microprocessors that can be debugged through the ARM's Serial Wire Debug (SWD) interface. Flashing targets is also done through it. This paper provides insights of the software and hardware behind a multiplexer that would allow to program multiple targets of the same model and type without the need of writing complex configuration scripts.